ENVIRONMENTAL SCIENCE AND SUSTAINABLE DEVELOPMENT: BEHAVIORAL TRANSFORMATION TO KNOWLEDGE SYSTEM INTEGRATION FOR SUSTAINABILITY ACTION - Sodri, Ahyahudin; Herdiansyah, Herdis (UI Scholars Hub, 2025)
Sustainability issues are now a global concern. However, knowing the root causes of problems and the target is not the only factor that constantly motivates change for the better (Wamsle & Osberg, 2022) as such change also requires encouragement from actors, including individuals, organizations, and communities. Therefore, the human aspect is crucial for the successful achievement of sustainability (Hariram et al., 2023). In other words, questions on sustainability are not just about